Mech jako materiał do uszczelniania belek w budownictwie drewnianym Karpat - Łuczaj, Łukasz; Grodzki, Witold; Marcela, Agnieszka (Studia Etnologiczne i Antropologiczne, 2021)
The article examines the tradition of the chinking of log cabins with moss in chosen villages of the Carpathian Foothills (SE Poland) in the counties of Krosno, Strzyżów, and Sanok. Moss used to be the main material used for chinking. After being gathered in pastures and forests by children and women, it was dried, sprinkled with water and packed with the help of the metal part of a plough. For the most efficient chinking, the space between logs had to be about 5 cm wide. The main species of moss used for this purpose were Rhytidiadelphus squarrosus (collected on pastures) and Pleurozium schreberi (collected in pine forests). The 1940s and 1950s saw a gradual discontinuation of this practice. In the course of the research, the author chinked two houses in cooperation with a person who was also a key source of information. The article also addresses the legal limitations of reviving the tradition, which include laws concerning the collecting of understorey plants in state forests, fines for using plants from other owners’ forests, and the protection of some moss species.